Administração e jogadas de xadrez: uma metáfora para o desenvolvimento de habilidades gerenciais e de liderança na formação de estudantes de Administração no Alto Solimões - Águila, João Tumbes (Brasil, 2023)
Chess is a strategic game that involves planning and decision making, fundamental elements in Administration. Similarities between the principles of chess and those of Management suggest that the game may be a valuable tool for the development of skills and competences in students of this area of knowledge. The aim of this study was to understand how the strategic principles of chess are related to the education of Administration students, regarding the development of their managerial and leadership skills and competences. Forty interviews were conducted with students of the Administration course of the Institute of Nature and Culture - INC/UFAM, through Google Forms. The data were imported from the Google Forms and analyzed using the Microsoft Excel 2019 program. The main results of this research show that 50% of respondents have already had some kind of contact with the game, besides highlighting the subject of Organizational Strategy and Organizational Management as relevant in the process of their training. The results of the survey also show that 80% of the students would like to have chess in the university environment. It is concluded that the use of chess as a teaching tool in the university environment can provide an innovative and motivating approach in the development of managerial and leadership skills in students of the Administration course, recommending that the institution adopts this approach as part of the curriculum, promoting a more complete training.